Pertumbuhan dan Hasil Tanaman Bayam (Amaranthus sp) pada Berbagai Komposisi Nutrisi Alternatif Pengganti AB Mix dengan Sistem Hidroponik Deep Flow Technique - Fitra Gustiar; Munandar Munandar; Nyayu Resti Aprilia; Mery Hasmeda; M Amar; Arsi Arsi (Seminar Nasional Lahan Suboptimal, 2021)
Gustiar F, Munandar M, Aprilia NR, Hasmeda M, Amar M, Arsi A. 2021. Growth and Yield of Spinach (Amaranthus sp) in various compositions of Alternative Nutrients to replace AB Mix with Hydroponic System.  In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 931-940 . Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). The high cost of AB Mix hydroponic nutrients, so there is a need for alternative growth nutrients that are cheaper and easily available. Aim of this research was to determine the hydroponic nutrition substitute for AB mix for the growth of spinach (Amaranthus sp). This study used a completely randomized design (CRD) method with four hydroponic nutrition treatments with different ingredients. The treatments given were AB mix fertilizer, NPK-based nutrition, single fertilizer-based nutrition, and organic nutrients. hydroponic nutrient constituents are calculated based on the needs of leaf vegetable plants. Needs Parameters observed were plant height (cm), number of leaves, leaf greenery level, leaf area (cm2), root volume (ml3), plant fresh weight (g), plant dry weight (g), and nitrogen concentration (N) at leaf. Based on the observation of growth parameters, AB mix nutrition treatment showed the best results. However, the fresh weight parameter of the single fertilizer-based nutrient treatment showed results that were not significantly different from the ABmix treatment. In addition to providing the highest yield, the lowest cost requirement is 1 liter of concentrate at a cost of 44,302 IDR so that single fertilizer-based hydroponic nutrients can be recommended as an alternative to AB Mix nutrition.